The Effectiveness of Flip Classroom with Student Teams-Achievement Divisions (STAD) Method to Teach Reading Viewed from Students’ English Learning Interest - Sunarti, Sunarti; Rachman, Dzul (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
The study is aimed: (1) To know whether Flip Classroom with STAD method is more effective than Traditional Instruction to teach reading; (2) to know whether the students who have high learning interest have better reading comprehension than those who have low learning interest; and (3) to know whether there is an interaction between Flip Classroom with teaching methods and students’ learning interest. The population of the research is the First year students of Public Health. The samples were from two classes. In taking the sample, cluster random sampling approach was used. Each class was divided into two groups (the students who have high and low learning interest). Then, the techniques which have been used to accumulate the information had been questionnaire student learning interest and reading test. The data were analyzed by using multifactor analysis of ANOVA 2x2 and Tuckey test. There are some research findings: (1) Flip Classroom with STAD method is more effective than Traditional Instruction to teach reading; (2) the reading comprehension of the students who have high learning interest is better than that of those who have low learning interest because; and (3) there is an interaction between teaching methods and learning interest for teaching reading. It is concluded that there is an interaction impact among methods and students’ learning interest for teaching reading. Flip Classroom with STAD is suitable for students having high learning interest and Traditional Instruction is suitable for students having low learning interest.